Hope for winter : the true story of a remarkable dolphin friendship - Yates, David, 1963-; Hatkoff, Craig; Hatkoff, Juliana; Hatkoff, Isabella (Scholastic Inc., 2014)
Details the experiences of a dolphin who was rescued five years after the tailless dolphin, Winter, was rehabilitated by the same group, describing the efforts made by the Clearwater Marine team to save the injured animal they named Hope.